THE IMPACT OF LIVING ENVIRONMENT AND ECOLOGICAL FACTORS ON THE DEVELOPMENT OF CHRONIC LIVER DISEASES - Jalolov N. N.; Rakhimov B. B.; Sherqoziyeva G. F.; Sultonov E. Y. (Bright Mind Publishing, 2025)
This analytical article provides a comprehensive assessment of the living environment, ecological factors, and their influence on the development of chronic liver diseases (CLD). Air pollution, deterioration of drinking water quality, ingestion of toxic substances through food, the level of urbanization, socio-hygienic characteristics of residential areas, and population behavioral factors are considered major risk contributors to CLD etiology. According to Global Burden of Disease (2023), liver diseases rank among the top 10 leading causes of death worldwide, with more than 60% of the total burden attributed to environmental and behavioral determinants. The study evaluates the integrated effects of these risk factors based on scientific literature, statistical reports, and advanced epidemiological models.
Keywords: Chronic liver diseases; ecological factors; air pollution; living environment; hygiene; heavy metals; pesticides; urbanization; liver fibrosis; epidemiological analysis.